Outcomes following acute tocolysis prior to emergency caesarean section. (6th May 2020) - Buckley, Victoria A.; Wu, Joyce; De Vries, Bradley
Abstract : Aim: To determine if a policy recommending administration of terbutaline prior to emergency caesarean section improved arterial umbilical cord pH. Materials and Methods: This was a prospective audit between February 2018 and June 2019 among women who underwent a category one or two caesarean section. Neonatal cord gas results and perinatal outcomes were compared before and after the introduction of a policy recommending subcutaneous terbutaline prior to emergency caesarean section. Results: Among 423 women in the pre‐policy change cohort and 253 post‐policy change, there was no difference in arterial cord pH (median pH = 7.24 before the policy and median pH = 7.24 after the policy was introduced, P  = 0.88). There was no statistically significant difference in any perinatal outcome, apart from the median arterial cord lactate which was higher in the post‐treatment group (4.2 mmol/L vs 3.9 mmol/L, P  = 0.006). Maternal heart rate was higher (median 110 vs 95, P  < 0.0001) in the post‐treatment group. Breastfeeding was more common in the post‐treatment group (99% vs 95%, P  = 0.005). There was no difference in estimated blood loss or rate of post‐partum haemorrhage. A post hoc analysis according to treatment received, limited to caesarean section when the indication was suspected fetal compromise, demonstrated that among women who received terbutaline the rate of low pH (<7.1) was 3.8% (5/130) when terbutaline was given, compared with 6.6% (18/272) when terbutaline was not given (χ 2 1  = 1.3, P  = 0.26). Conclusion: Changing our labour ward policy to recommending terbutaline prior to all category one and category two caesarean sections did not change arterial cord pH.